Melatih Kemampuan Bahasa Verbal Anak Usia 0-3 Tahun Melalui Kegiatan Membacakan Buku - Sumiyati, Sumiyati (UIN Sultan Maulana Hasanudin Banten, 2026)
The purpose of this study is to determine the verbal language abilities of children aged 0-3 years through book reading activities. This research is motivated by empirical evidence that most of the children at Mozaik Al Mecca Daycare experience speech delay. Therefore, verbal language skills must be stimulated from an early age, so that children can have a large vocabulary and be able to communicate verbally well. This research is a qualitative descriptive type based on case studies. Data in this study were collected through interviews, observations, and document studies. The results indicate that reading books has a significant impact on children's verbal language skills at Mozaik Al Mecca Daycare. This is shown by the child's ability to respond to the educator, imitate the words taught by the educator, and the ability to imitate mouth movements exemplified by the educator for children who have not yet achieved speaking skills. The habit of reading books is very important so that children have optimal verbal language skills, whether carried out by educators or by parents at home.